2018
DOI: 10.1177/1078155218805539
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival in patients with metastatic malign melanoma treated with ipilimumab: Turkish Oncology Group study

Abstract: Purpose Studies in the last decade show survival improvement with checkpoint blocker therapy in patients with metastatic malign melanoma. Our purpose was to define the efficacy of ipilimumab according to the patient's baseline characteristics including absolute lymphocytes count. Methods We collected the data of 97 patients with advanced malign melanoma treated with ipilimumab (3 mg/kg, q3w) retrospectively. Log-rank test was used to analyze the univariate effects of patient's characteristics (age, gender, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…A low TLC level before any medical intervention is a well-known predictor of mortality [5] , [6] , [7] , [8] , [9] , [10] . Studies have shown an increased risk of death in ICU-acquired pneumonia (hazard ratio, HR 1.41; TLC < 595 cells/µL) [5] , cardiac surgery (OR 1.01 for each reduction of 10 cells/µL in TLC) [7] , intestinal surgery (HR 9.09; no cut-off point was defined) [10] , gastric cancer surgery (HR 1.97; TLC < 1462 cells/µL) [6] , chemotherapy for melanoma (unspecified risk; TLC < 1500 cells/µL) [23] , clinical treatment of lung cancer (HR 1.81; TLC < 1900 cells/µL) [8] , surgery for femoral neck fractures (OR 1.45 for each reduction of 100 cells/µL in TLC) [9] , and surgery for appendicular pathological fractures (unspecified risk; TLC < 600 cells/µL) [19] .…”
Section: Discussionmentioning
confidence: 99%
“…A low TLC level before any medical intervention is a well-known predictor of mortality [5] , [6] , [7] , [8] , [9] , [10] . Studies have shown an increased risk of death in ICU-acquired pneumonia (hazard ratio, HR 1.41; TLC < 595 cells/µL) [5] , cardiac surgery (OR 1.01 for each reduction of 10 cells/µL in TLC) [7] , intestinal surgery (HR 9.09; no cut-off point was defined) [10] , gastric cancer surgery (HR 1.97; TLC < 1462 cells/µL) [6] , chemotherapy for melanoma (unspecified risk; TLC < 1500 cells/µL) [23] , clinical treatment of lung cancer (HR 1.81; TLC < 1900 cells/µL) [8] , surgery for femoral neck fractures (OR 1.45 for each reduction of 100 cells/µL in TLC) [9] , and surgery for appendicular pathological fractures (unspecified risk; TLC < 600 cells/µL) [19] .…”
Section: Discussionmentioning
confidence: 99%
“…We thank Yilmaz and colleagues for their comments on our study that was evaluated ''Prognostic factors for survival in patients with metastatic malign melanoma treated with ipilimumab: Turkish Oncology Group study''. 1 The authors specifically question whether radiotherapy is associated with ipilimumab clinical efficacy in our study.…”
mentioning
confidence: 86%
“…Cox regression analysis revealed that Response Evaluation Criteria in Solid Tumors (RECIST) response (complete or partial response), absolute lymphocytes count (more than 1500/mm 3 ) and the number of metastatic sites (less than three sites) were independent prognostic factors for longer survival. 1 In our cohort, 36 patients (37%) received radiotherapy, vast majority of patients received palliative radiation (34 patients) therapy. In 39% of patients, radiation was administered within three months of ipilimumab administration.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We read the article entitled “Prognostic factors for survival in patients with metastatic malign melanoma treated with ipilimumab: Turkish Oncology Group study” with great interest. 1 We want to congratulate the authors for their effort to detect prognostic factors for overall survival in patients with metastatic malign melanoma using ipilimumab. For those of us who have witnessed the opening of the era of immunotherapy, series with a large number of patients should be appreciated, while even the smallest information crumbs are worthwhile to understand this new treatment modality.…”
mentioning
confidence: 99%